Effectiveness of the Medical Command System in Catastrophic Emergency Response at Grandmed Hospital Lubuk Pakam and Sembiring General Hospital Delitua in 2023 - Wiratma, Dicky Yuswardi (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The Medical Command System (MCS) is a crucial mechanism in hospital disaster management to ensure effective coordination, communication, and resource allocation. This study aimed to evaluate the effectiveness of the MCS in catastrophic emergency response at Grandmed Hospital Lubuk Pakam and Sembiring General Hospital Delitua in 2023. Methods: This study employed a descriptive quantitative design with a survey approach. Data were collected using questionnaires covering indicators of coordination, communication, and resource allocation. Respondents consisted of healthcare workers involved in hospital disaster response teams. Results: The findings revealed that the effectiveness of MCS implementation reached 85% at Grandmed Hospital and 77.7% at Sembiring General Hospital. Grandmed Hospital demonstrated better preparedness in logistics and command structure, while Sembiring Hospital faced challenges in communication facilities and emergency logistics availability. Key barriers included limited communication infrastructure, lack of routine simulations, and suboptimal staff training. Conclusion: The MCS was proven effective in supporting catastrophic emergency response in both hospitals. However, further improvement in communication systems, disaster simulation, and emergency logistics management is needed to strengthen hospital disaster preparedness.